The religious legacy of śiwa-buddha at Kalibukbuk temple, Buleleng: A historical and religious approach - Widyastuti, Ni Putu (Dharmakirti : International Journal of Religion, Mind and Science, 2024)
Background: This study explores the religious legacy of Śiwa-Buddha at Kalibukbuk Temple in Buleleng, aiming to highlight the historical and religious aspects that contribute to its significance. The integration of Śiwa and Buddha traditions in Balinese religious culture reflects the island’s parallel religious landscape, particularly during the Majapahit era. Previous studies have discussed the blending of Śiwa and Buddha elements in various Balinese temples, yet there is limited focused research on Kalibukbuk Temple. This study addresses this gap by analyzing historical records and religious texts, shedding light on how the Śiwa-Buddha harmonization shaped local religious practices. Methods: The research utilizes a qualitative method with a historical-analytical approach, combining literature review, field observations, and interviews with religious practitioners. Data collection involved an examination of temple inscriptions, carvings, and architecture to interpret symbolic elements related to Śiwa-Buddha teachings. A comparative analysis with similar temples in Bali was also conducted to emphasize common patterns and distinctive characteristics. Findings: The findings indicate that Kalibukbuk Temple serves as a cultural and spiritual focal point in Buleleng, with Śiwa-Buddha elements prominently reflected in its architectural design, deity iconography, and ritual practices. The temple’s inscriptions reveal a deliberate effort to harmonize Śaivism and Buddhism, which suggests an inclusive religious policy of the era. Furthermore, the study shows that this religious harmonization at Kalibukbuk facilitated greater social cohesion within the local community by bridging religious differences. Conclusion: In conclusion, the study reveals that the Kalibukbuk Temple's religious legacy illustrates a successful integration of Śiwa-Buddha traditions, reflecting Bali’s broader harmonized religious identity. Novelty/Originality of this article: The novelty of this research lies in its focused examination of a lesser-studied temple, providing fresh insights into Balinese religious history. This study contributes to the understanding of how religious harmonization played a vital role in shaping cultural and religious continuity in Bali.